Safety of Intravenous Iron in CKD Stage 3-5 Patients Not on Dialysis: A Retrospective Cohort Study - Ali AlSahow; Anas AlYousef; Hani Nawar; Bassam AlHelal; Ahmed AlQallaf; Abdullah AlMuhaiteeb; Yasser ElSharkawi; Heba AlRajab; Hamad Ali; Rajeev Kumar (Canadian Journal of Kidney Health and Disease, 2022)
Background: Iron deficiency is common in chronic kidney disease (CKD) patients not on dialysis (ND). Restoring depleted iron stores through intravenous (IV) route is faster and associated with less side effects. There is conflicting data regarding intravenous iron use and its impact on clinical outcomes in this population. Objective: This study aims at evaluating any negative clinical impact associated with IV iron use in CKD patients at stages (3-5) before dialysis. Design: Retrospective chart review. Setting and Population: Chart analysis of ND CKD 3-5 (estimated glomerular filtration rate [eGFR] <60 mL/min/1.73 m 2 ) patients who received IV iron between January 2013 and January 2018 in 3 major hospitals in Kuwait. Methods: Outcomes analyzed were rates of all-cause hospitalizations, infection-related hospitalizations, mortality rates, and eGFR decline over 12 months after IV iron infusion in this population divided into 3 groups according to CKD stage. Results: A total of 738 patients were included in our analysis. Mean initial hemoglobin concentration was 111.5 ± 15.0 g/L in group 1 (CKD 3: eGFR 30-59 mL/min/1.73 m 2 ), 103.6 ± 17.7 g/L in group 2 (CKD 4: eGFR 15-29 mL/min/1.73 m 2 ), and 99.4 ± 14.5 g/L in group 3 (CKD 5: eGFR < 15 mL/min/1.73 m 2 but not on dialysis). All-cause hospitalization and infection-related hospitalization were more common among group 3 subjects (adjusted odds ratio =2.12 [95% confidence interval, CI: 1.32-3.41] and 2.02 [95% CI: 1.15-3.55]), respectively. No deaths occurred during 12 months of follow-up. Limitations: Lack of control group, retrospective study. Conclusion: Intravenous iron use in CKD 3-5 ND is generally safe. Higher hospitalization rates in patients with eGFR <30 mL/min are possibly associated with lower baseline hemoglobin, lower baseline eGFR, and higher comorbidity burden, and not related to iron infusion.